Kate Chopin`s early fiction as a prologue to the emergence of the new woman - Khoshnood, Ali; Talif, Rosli; Lalbakhsh, Pedram (Universiti Putra Malaysia Press, 2013)
Despite the revival of interest in Kate Chopin’s works during the twentieth century, her early fiction has not yet elicited as much critical appreciation as The Awakening has. The aim of this study is to show that Chopin’s first novel, At Fault, and the tale, “Lilacs”, exhibit the same genius and modern forms and features of her later fiction. Chopin’s authorial voice, strongly but covertly, addresses society’s flaws which are rooted in the illogical demands of the Christian religion and male moral philosophy. This study attempts to demonstrate that Chopin’s hidden anti-religious sentiment is one of her earliest attacks on the role of the Church in prescribing religious codes and social mores and that Chopin blames the Church for being indifferent to women’s needs. Although Chopin portrays female characters who feel constrained by the societal definition of their duties and responsibilities, she shows them enjoying various means of satisfaction and fulfillment. In spite of that, however, they experience a decisive transformation in their religious lives and mentality. The protagonists that Chopin depicts share some traits, ideals and visions of the New Woman, but their interests diverge according to their different needs. This study attempts to introduce Chopin’s portrayal of her protagonists as early versions of the New Woman that can promise fuller and a more complex emergence in her later fiction.